Cybercrimes in the former Soviet Union and Central and Eastern Europe: current status and key drivers - Kshetri, Nir (Crime, law and social change, 2013)
Some economies in the Former Soviet Union and Central and Eastern Europe (FSU&CEE) are known as cybercrime hotspots. FSU&CEE economies have shown complex and varied responses to cybercrimes due partly to the differential incentives and pressures they face. This study builds upon literatures on white-collar crime, institutional theory and international relations (IR)/international political economy (IPE) perspectives to examine the low rates of prosecution and conviction of suspected cybercriminals in some economies in the FSU&CEE and variation in such rates across these economies. The findings indicate that cybercrime cases are more likely to be prosecuted and sanctions are imposed in economies that are characterized by a higher degree of cooperation and integration with the West. Cybercriminals are less likely to be jurisdictionally shielded in such economies. Our findings also suggest that a high degree of cooperation and integration with the West would lead to access to resources to enhance system capacity and law enforcement performance to fight cybercrimes.